GRAMATICAL ERRORS OF SHORT STORY BY BLOGGER IN INTERNET - syarifah ilma (Department of Master of Linguistic, Universitas Airlangga, 2021)
English is not second language of Indonesia, so lot of them has lot of Errors when they are learning English, one of them is grammar error, in this research will talk about the grammar error and the correction of short story, also discuss about what is the errors of this story and what are they, in this reseach has some purpose to study about grammar errors. This writing was carried out for research on how many grammatical errors in the content of a blogger on the internet, in this study the author uses the method of error analysis.The results of this study indicate several aspects of error, namely, Errors in the use of groups of verbs, Errors in the use of prepositions, Errors in the use of pronouns, Errors in the use of adverbs, this is due to several factors, one of which is because English is their second language. and not the first language, etc.